Strengthening Sharia Crowdfunding Law through the Maqasid al-Shari'ah Approach: An Analysis of Financial Services Authority Regulation (POJK) - Maryani Maryani; Irvan Irvan; Zelki Marfinas; M. Raihan Habibillah; Deni Kurnia; M. Ridho Pratama (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
The rapid growth of Indonesia’s sharia digital economy has created new financing models, particularly sharia crowdfunding, as an inclusive alternative for MSMEs. However, the current regulatory framework Financial Services Authority Regulation (POJK) No. 16/POJK.04/2021, remains general and has not fully incorporated sharia compliance principles. This study aims to analyze the strengthening of sharia crowdfunding law through the Maqasid al-Shari‘ah approach, emphasizing maslahah (public welfare), hifz al-m?l (protection of wealth), and ‘adl (justice). Using a normative legal method that combines statute and conceptual approaches, this research evaluates the extent to which POJK No. 16/2021 aligns with Islamic legal objectives. The findings show partial conformity, strong in procedural governance but weak in substantive justice and sharia supervision. The absence of a Sharia Supervisory Board (DPS) and explicit sharia audit requirements limits regulatory effectiveness. The study recommends reconstructing POJK No. 16/2021 through an integrated sharia governance system involving OJK, DSN-MUI, and halal certification bodies. Mandatory sharia audits, digital financial literacy, and value-based supervision are proposed to enhance ethical accountability. Such reform would harmonize technological innovation with the moral imperatives of Maqasid al-Shari‘ah, positioning Indonesia as a global pioneer in Islamic digital finance.